2017
DOI: 10.1021/acs.jafc.7b04442
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Screening of a Novel, Moderately Hydrophilic Angiotensin-Converting-Enzyme-Inhibitory Peptide, RYL, from Silkworm Pupa Using an Fe-Doped-Silkworm-Excrement-Derived Biocarbon: Waste Conversion by Waste

Abstract: A novel, moderately hydrophilic peptide (RYL) with high ACE-inhibitory activity was screened ultrafast via a concept of waste conversion using waste. This novel peptide was screened from silkworm pupa using an Fe-doped porous biocarbon (FL/Z-SE) derived from silkworm excrement. FL/Z-SE possessed magnetic properties and specific selection for peptides due to Fe's dual functions. The selected RYL, which has moderate hydrophilicity (LogP = -0.22), exhibited a comparatively high ACE-inhibitory activity (IC = 3.31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Some of them were found to exert two or more activities. Thus, α s1 -CN-derived peptides RY, RYL, RYLG, YLGY and FYPEL exert both ACE-inhibitory and antioxidant activities [ 23 , 24 , 25 , 26 , 27 ]. ACE-inhibitory and opioid activities are exerted by sequences YGFLP [ 28 ] and YGFL [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some of them were found to exert two or more activities. Thus, α s1 -CN-derived peptides RY, RYL, RYLG, YLGY and FYPEL exert both ACE-inhibitory and antioxidant activities [ 23 , 24 , 25 , 26 , 27 ]. ACE-inhibitory and opioid activities are exerted by sequences YGFLP [ 28 ] and YGFL [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Competitive inhibitors can compete with the substrate for the catalytic site of the enzyme or can alter the conformation of the enzyme, ultimately inhibiting its activity [ 43 ]. In recent years, many competitive ACE inhibitory peptides have been reported, such as YQK (Tyr-Gln-Lys) from bovine casein [ 44 ], RYL (Arg-Tyr-Leu) from Silkworm Pupa [ 45 ], VVSLSIPR (Val-Val-Ser-Leu-Ser-Ile-Pro-Arg) from pigeon pea ( Cajanus cajan ) [ 46 ], and YLYELAR (Tyr-Leu-Tyr-Glu-Leu-Ala-Arg), AFPYYGHHLG (Ala-Phe-Pro-Tyr-Tyr-Gly-His-His-Leu-Gly) from scorpion ( Hemiscorpius lepturus ) venom. In addition, commercial functional foods or dietary supplements [ 16 , 17 ], as well as many antihypertensive drugs [ 47 ], have also been reported to be competitive inhibitors of ACE.…”
Section: Resultsmentioning
confidence: 99%
“…Authors used docking to study the mode of action of both peptides. In other work, Liu et al [24] found a hydrophilic peptide (RYL) derived from agricultural waste (silkworm excrement and pupa) with high ACE-inhibitory activity. Authors used docking to study interactions between RYL and its target.…”
Section: Molecular Modeling Applied To the Study Of Ace Inhibitors Inmentioning
confidence: 98%